An Investigation into Artificial Intelligence Knowledge to Support Science Learning among Junior High School Students - Nisa , Jauha Khoirun; Fibriana, Fidia (Universitas Negeri Semarang, 2025)
Artificial Intelligence (AI) has rapidly become an essential component of digital learning environments, making AI literacy increasingly important for junior high school students. This study investigates students’ knowledge of AI, the frequency of AI use, and the role of AI in supporting science learning. A descriptive quantitative design was employed, involving 136 seventh-grade students who completed a validated questionnaire via Google Forms. The data were analyzed using descriptive statistics to identify patterns in AI familiarity and utilization. Results indicate that although 92.6% of students have heard of AI and 63.2% have used it in general learning activities, the frequency of AI use in science learning remains low, with 78.7% reporting infrequent use. Students primarily rely on AI for textual explanations and homework completion, yet many express concerns about the accuracy of AI-generated information. The study highlights a substantial gap between students’ awareness of AI and their ability to engage with it meaningfully in science learning contexts. These findings underscore the need for targeted AI literacy programs and structured pedagogical strategies that guide ethical, critical, and inquiry-based uses of AI in science education. Integrating AI meaningfully in the curriculum may strengthen students’ scientific reasoning and digital competencies.